Statistical methods for handling observation clustering in sports injury surveillance - Chandran, A.; Brown, D.; Nedimyer, A. K.; Kerr, Z. Y. (Journal of Athletic Training, 2019)
Context: Advances in sports injury-surveillance methods have made it possible to accommodate non-time-loss (NTL) injury reporting; however, the analysis of surveillance data now requires careful consideration of the nuances of NTL injury records.